Body shape and mode of propulsion do not constrain routine swimming in coral reef fishes. (27th November 2022) - Satterfield, Darien R.; Claverie, Thomas; Wainwright, Peter C.
Abstract: It is widely believed that because of biomechanical trade‐offs, fish body shape and the mode of propulsion are strong predictors of swimming performance, with the best cruisers, maneuverers and accelerators having different body forms and emphasizing different propulsion mechanisms. This paradigm is regularly projected onto routine swimming behaviour and dominates the ecomorphological literature, despite the paucity of field measurements. In this study, we measured variation in swimming behaviour among 48 species of Indian Ocean coral reef fishes using recordings from a remote stereo video system. We measured average swimming speed, average swimming bout distance, frequency of turns and percent of time spent station‐holding and looked for the predicted trade‐offs between them. We find little evidence of the expected relationships between swimming behaviours across species, little evidence that body shape affects swimming and few differences between species that swim by undulating the body and those that emphasize the use of median and paired fins. Taxa widely thought of as archetypical maneuverers ( Chaetodon ) and cruisers ( Caranx ) were not outliers in any behaviours. Our results indicate that swimming behaviour is not easily predicted from simple measures of body shape and that alternative swimming modes can produce comparable behavioural profiles. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.